Fabrication of MoSe2 nanoribbons via an unusual morphological phase transition - Yuxuan Chen (Nature Portfolio, 2017)
The unique electronic properties of two-dimensional materials are determined not only by their shape, but also the precise atomic arrangement of atoms along edges. Here, Chenet al. have developed a bottom-up epitaxial growth of MoSe2nanoribbons that controls both geometry and edge states.